Influence of COVID-19 lockdown on noise level reduction: a scoping review with stakeholders’ consultation - Helmi, Amirul Aiman; Romli, Muhammad Hibatullah; Ezani, Eliani (Universiti Putra Malaysia Press, 2023)
EIn light of the COVID-19 pandemic, empirical evidence suggests that the global community has commenced a recuperation process and witnessed a notable positive influence. Despite several published research on the topic, a complete analysis examining the effects of lockdown measures implemented during the COVID-19 pandemic on environmental noise has yet to be conducted. Thus, this scoping review with stakeholders’ consultation was conducted to systematically identify literature related to noise level reduction. An electronic search was conducted up to August 8, 2020, on four databases (Science Direct, SCOPUS, CINAHL, and PubMed). Eight articles met our criteria for further review where G20 countries conducted most studies. Three were reviewed, two were experimental, two were case reports, and the other was protocol. Although the current literature is minimal, it is evident that global noise levels are decreasing significantly. However, our review revealed that none of the included studies addressed the effect of noise level reduction on human health, and we view the decrease not necessarily as an outcome of the COVID-19 pandemic outbreak but rather because of the transition from outdoor to indoor environments. As this subject matter has received a lack of attention and is often overlooked, more innovative research to look for state-of-the-art stagnant initiatives is needed to control the issue of noise pollution and to provide a basis for government policies.